Larval development of nypa palm worm Namalycastis rhodochorde (Polychaeta: Nereididae) - Junardi Junardi; Tjandra Anggraeni; Ahmad Ridwan; Edy Yuwono (Smujo International, 2020)
Abstract. Junardi, Anggraeni T, Ridwan A, Yowono E. 2020. Larval development of nypa palm worm Namalycastis rhodochorde (Polychaeta: Nereididae). Nusantara Bioscience 12: 148-153. Namalycastis intensive culture is still facing problems in mass production due to limited information on reproduction, especially in fertilization and production of larvae. The present research was designated to find out optimum salinity for fertilization and the production of nypa palm worm larvae (Namalycastis rhodochorde). Gamete samples were collected using a capillary glass tube inserted into ventro-lateral part of a body segment of a mature worm. Artificial fertilization was done by mixing the sperms and oocytes in a fertilization dish containing sterilized seawater as the medium. The larval development was observed until the benthic phase larvae (3-setigers). Fertilization was performed in medium salinity of 7-21‰ and water temperature of 25-29°C. The cleavage and larva stage occurred respectively within 28.20 to 58.67 minutes and within 72 to 80 hours after fertilization. The fertilization and larval development of N. rhodochorde were highly influenced by the medium salinity and temperature.